Mass modeling of Malaysian varieties pomelo fruit (Citrus Grandis L. Osbeck) with some physical characteristics - Buang, Nur Salihah; Shamsudin, Rosnah; Ab. Aziz, Norashikin (Faculty of Food Science and Technology, Universiti Putra Malaysia, 2015)
Knowledge of physical characteristics of Malaysian variety pomelo fruits are necessary for the design of some post harvesting, processing systems such as cleaning, handling, grading and packaging system. For proper development of pomelo grading systems, important relationships between the mass and some physical characteristics of pomelo fruits such as length, width, thickness, surface area, projected areas and volumes must be known. The aim of this research was to measure physical characteristics of two Malaysian varieties of pomelo fruit; Ledang (PO55) and Tambun (PO52) varieties. In this study, the mass of pomelo fruit was evaluated and correlated to measure physical characteristics using Linear, Quadratic, S-curve and Power models. The results showed that the correlation of the mass of pomelo fruit with all measured physical characteristics was significant at the 0.01 probability level. In the nutshell, mass modeling of pomelo fruit for Ledang (PO55) and Tambun (PO52) varieties based on the projected area are recommended according to economical view.